Sustainability perspectives in agricultural economics research and policy agenda - Bernardo C. De Gennaro; Maria Bonaventura Forleo (Agricultural and Food Economics, 2019)
The agricultural sector both needs to reduce its impacts and adapt its food production system to cope with environmental constraints and climate changes. This special issue includes three selected papers presented at the 53rd annual Conference of the Italian Society of Agricultural Economics discussing the future of agriculture. The fil rouge linking the three papers is the issue of sustainability that nowadays influences the functioning of the food supply chain and the behavior of all actors involved in it, from producers to consumers.
Keywords: 330; Climate change; Sustainable innovations; Wine purchasing behavior; Millennials